Was there an original causeway across the Antonine Wall ditch at Rough Castle? - Hanson, W S (Proceedings of the Society of Antiquaries of Scotland, 2024)
It has long been accepted that the Antonine Wall ditch in front of the north gate of the fort at Rough Castle was provided with an undug causeway, implying that the existence of the fort was known at the time the ditch was dug. This has created problems for our understanding of the chronology of the Wall construction process because it contradicts other stratigraphic evidence that the fort was a later addition. The evidence for the existence of a primary causeway is challenged, based on an examination of archival photography and a re-assessment of the early excavation data supported by historical mapping and LiDAR data, concluding that it can no longer be sustained.